Geochemical characteristics of Late Glacial and Holocene biogenic sediments in central Poland and implications for reconstructing the palaeoenvironment - Okupny, Daniel (Acta Geographica Lodziensia, 2023)
The chemical composition of lake and mire sediments can be used as proxies of past changes in different accumulation environments. Here, I present these proxies that can be used to reconstruct the palaeoenvironment of the past 16,000 years for many mineral-biogenic series from central Poland and establish regional similarities and differences. Past geochemical studies of biogenic sediments from this region were usually carried out in the context of the genesis of: individual accumulation reservoirs, the development of the relief of river valleys and watersheds; they were also used in combination with other methods of palaeoecological research also reconstruct climatic changes in individual phases of the Late Glacial and Holocene. However, due to the complexity of matter circulation in the lithological and hypsometrical diverse transitional zone between the belts of the Polish Uplands and the Polish Lowlands, an analysis was made to determine the relationship between the conditions of biogenic sedimentation at individual sites using selected statistical analyses. In addition to its description of the geochemical variability of biogenic sediments, this analysis was supplemented by its reference to the spatial differentiation in the relationships between geochemical landscapes and the landforms of various orders. In turn, the method of lithogeochemical facies used for several profiles along the transect from the west to the east of the region made it possible to determine: the origin of water supplying the studied biogenic accumulation reservoirs, the range of individual zones of their supply and the conditions of inflow of allochthonous mineral matter.